15x^2 − 4x + x^2 + 9x − x − 6x^2 =

  • 1 view

15x^2 − 4x + x^2 + 9x − x − 6x^2 = ?First you can break up the question and sort out the x^2 part of the equation to make it easier: 15x^2 + x^2 − 6x^2 = 10x^2Then you are left with solving the second part of the equation which is: -4x + 9x - x = 4xWhen these two sections are then combined to complete the equation you get: = 10x^2 + 4xShowing that 15x^2 − 4x + x^2 + 9x − x − 6x^2 = 10x^2 + 4x

Looking for more help? Search our library of answers.👇

Need help with Maths?
Boost your grades with stress-free tuition that fits your schedule.

About the author

Jonjo H. is an online Maths tutor with MyTutor studying at Manchester (Computer Science) University

mtw:mercury1:status:ok